Circumarctic Landcover Units - Bartsch, Annett; Khairullin, Rustam; Efimova, Aleksandra; Widhalm, Barbara; Muri, Xaver; von Baeckmann, Clemens; Bergstedt, Helena; Ermokhina, Ksenia; Hugelius, Gustaf; Heim, Birgit; Leibman, Marina; Gruber, Chiara (Zenodo, 2024)
Landcover units have been derived from Copernicus Sentinel-1 und Sentinel-2 data acquired between 2016 and 2024 for the Arctic tundra biome and selected adjacent areas. 23 units of which 20 represent different vegetation characteristics and soil conditions are differentiated. The units have been identified with K-means over a representative transect and in a second step retrieved across the entire Arctic north of the treeline. The description of the units is based on several thousand samples from vegetation surveys and soil probes. The units are supplied at 10m resolution in 17 irregular tiles. Auxiliary data for quality information and input acquisition dates are supplied in a separate file (polygons with attributes). Units are documented in detail in the product user guide (PUG) and in Bartsch, A., Efimova, A., Widhalm, B., Muri, X., von Baeckmann, C., Bergstedt, H., Ermokhina, K., Hugelius, G., Heim, B., and Leibman, M.: Circumarctic land cover diversity considering wetness gradients, Hydrol. Earth Syst. Sci., 28, 2421–2481, https://doi.org/10.5194/hess-28-2421-2024, 2024. For separation of artificial surfaces it is recommended to combine the units with: Bartsch, A., Widhalm, B., von Baeckmann, C., Efimova, A., Tanguy, R., & Pointner, G. (2023). Sentinel-1/2 derived Arctic Coastal Human Impact dataset (SACHI) (v2.0) [Data set]. Zenodo. https://doi.org/10.5281/zenodo.10160636